4 Relationship between blood pressure level and hypertensive mediated organ damage. (22nd March 2023) - Setjiadi, Dellaneira; Delles, Christian; Currie, Gemma; Celis-Morales, Carlos A
Abstract : It is well-known that blood pressure (BP) level correlates with hypertension-mediated organ damage (HMOD), however, a disproportional degree of organ damage in relation to BP level has been observed clinically. The study aims to quantify the proportion of discrepancy between BP level and HMOD severity including its risk factors. This cross-sectional study includes 268 participants from the UK Biobank cohort study (49.6% were females, mean age 56 years). The independent variable was BP including systolic BP, diastolic BP and pulse pressure (PP). Arterial stiffness measured by pulse wave velocity (PWV) was the marker used as a proxy of HMOD. To identify outliers for each of these variables a 0.5 standard deviation (SD) above or below the mean was used as cut-off point. The association between BP and HMOD variables were investigated using regression analysis. Preliminary results using PWV variables showed that 67 and 44 participants were classified as outliers for PWV and BP, respectively. Men were more likely to be outliers than women for PWV while women were more likely to be an outlier for SBP. Participants aged <56 years were also more likely to be outliers for PWV and BP than their older counterparts. No difference on the numbers of outliers were observed across BMI categories. Analysis using complete variables is necessary to conclude results from this study and its application in clinical practice.